Eredoctoraat dr.h.c. Jeroen Brouwers - Brouwers, Jeroen; Joosten, Jos; Vandenbroucke, Johan (Radboud University Press, 2024)
On 18 October 2018, during the 95th Dies Natalis, Jeroen Brouwers received an honorary doctorate from the Radboud University. This honorary doctorate was awarded to him because of his significance to Dutch literature. This edition includes the laudatio by the honorary promotor Jos Joosten, the acceptance speech by Jeroen Brouwers and a curriculum vitae by Brouwers' biographer Johan Vandenbroucke. Honorary promoter Jos Joosten described Jeroen Brouwers in 2018 as ""a prominent and highly acclaimed writer with a career spanning more than half a century. He has addressed important societal issues in his novels, such as the processing of the Second World War in the Dutch East Indies in 'Bezonken Rood' (1981) and the abuse in the Catholic Church in 'Het Hout' (2014). But he is also a great essayist, employing a method that lies between scholarly analysis and literary imagination, and a polemicist. He serves as an example for many writers: he lives for and through literature. As a critic, he also writes extensively about Flemish literature, which is also a particular focus of Nijmegen's Dutch studies. And whether he's engaging in polemics or erecting a statue for a writer: stylistically, it's always virtuoso.""